A Mixed-Methods Study on Patient Safety Insights of New Graduate Registered Nurses. Issue 3 (July 2020) - Murray, Melanie; Sundin, Deborah; Cope, Vicki
Abstract : Background: New graduate nurses transition with limited experience, and with anxiety and stress. They present an increased risk of contributing to preventable errors or adverse events. Purpose: The purpose was to develop an understanding of new graduate registered nurses' (RNs) patient safety knowledge and actions within the first year of registration. Methods: The longitudinal mixed-methods study was conducted using a questionnaire delivered at 3 time points (n = 68). Qualitative data were collected by semistructured interviews (n = 11). Results: Self-reported knowledge of medical error decreased over the 3 time points. Themes emerging from qualitative data include patient safety and insights, time management, making a mistake, experiential learning, and transition. Conclusions: Medical errors and time management persist during transition to the RN role. New graduates reported moderate knowledge of safety and quality issues; however, questioning their own abilities overshadowed growth in their involvement in patient safety. Abstract : Supplemental Digital Content is Available in the Text.